Summer Carbonate Chemistry in the Dalton Polynya, East Antarctica. Issue 8 (13th August 2019) - Arroyo, M. C.; Shadwick, E. H.; Tilbrook, B.
Abstract: The carbonate chemistry in the Dalton Polynya in East Antarctica (115°–123°E) was investigated in summer 2014/2015 using high‐frequency underway measurements of CO2 fugacity ( f CO2 ) and discrete water column measurements of total dissolved inorganic carbon (TCO2 ) and total alkalinity. Air‐sea CO2 fluxes indicate this region was a weak net source of CO2 to the atmosphere (0.7 ± 0.9 mmol C m −2 day −1 ) during the period of observation, with the largest degree of surface water supersaturation (Δ f CO2 = +45 μatm) in ice‐covered waters near the Totten Ice Shelf (TIS) as compared to the ice‐free surface waters in the Dalton Polynya. The seasonal depletion of mixed‐layer TCO2 (6 to 51 μmol/kg) in ice‐free regions was primarily driven by sea ice melt and biological CO2 uptake. Estimates of net community production (NCP) reveal net autotrophy in the ice‐free Dalton Polynya (NCP = 5–20 mmol C m −2 day −1 ) and weakly heterotrophic waters near the ice‐covered TIS (NCP = −4–0 mmol C m −2 day −1 ). Satellite‐derived estimates of chlorophyll a (Chl a ) and sea ice coverage suggest that the early summer season in 2014/2015 was anomalous relative to the long‐term (1997–2017) record, with lower surface Chl a concentrations and a greater degree of sea ice cover during the period of observation; the implications for seasonal primary production and air‐sea CO2 exchange are discussed. This study highlights the importance of both physical and biological processes in controlling air‐sea CO2 fluxes and the significant interannual variability of the CO2 system in Antarctic coastal regions. Plain Language Summary: Coastal polynyas in Antarctica are dynamic regions that play important roles in the global cycling of carbon. Polynyas are reoccurring areas of open water within sea ice and are often associated with enhanced rates of photosynthesis and exchange of carbon dioxide between the atmosphere and ocean surface. In this study, we use shipboard observations from the first oceanographic cruise in the Dalton Polynya near the Totten and Moscow University Ice Shelves in East Antarctica to characterize the inorganic carbon chemistry in the summertime. We find that the surface concentrations of total dissolved inorganic carbon are reduced in areas of open water mainly as a result of seasonal sea ice melt and the uptake of inorganic carbon by photosynthesis and less so due to air‐sea exchange of carbon dioxide. Compared to other coastal polynyas in East Antarctica, our results show that the Dalton Polynya may have smaller rates of net photosynthesis and carbon dioxide exchange. Key Points: The Dalton Polynya was a weak net source of CO2 to the atmosphere during summer observations Net community production estimates were 5‐20 mmol C m ‐2 day ‐1 in ice‐free and ‐4‐0 mmol C m ‐2 day ‐1 in ice‐covered regions Remotely sensed products reveal below average surface chlorophyll a and above average sea ice cover in contrast to long‐term summer means